Defensive weapons and star wars: a supergame with optimal punishments. Issue 4 (3rd July 2016) - Giacomello, Giampiero; Lambertini, Luca
Abstract : We model the perspective faced by nuclear powers involved in a supergame where nuclear deterrence is used to stabilise peace. This setting allows us to investigate the bearings of defensive weapons on the effectiveness of deterrence and peace stability, relying on one-shot optimal punishments. We find that the sustainability of peace is unaffected by defensive shields if the latter are symmetric across countries, while asymmetric endowments of such weapons have clear-cut destabilising consequences.